Postexercise cooling rates in 2 cooling jackets - Brade, Carly; Dawson, B.; Wallman, K.; Polglaze, T. (2010)
Context: Cooling jackets are a common method for removing stored heat accumulated during exercise. To date, the efficiency and practicality of different types of cooling jackets have received minimal investigation. Objective: To examine whether a cooling jacket containing a phase-change material (PC17) results in more rapid postexercise cooling than a gel cooling jacket and a no-jacket (control) condition. Design: Randomized, counterbalanced design with 3 experimental conditions. Setting: Participants exercised at 75% V? O2max workload in a hot climate chamber (temperature = 35.0 ± 1.4°C, relative humidity = 52 ± 4%) for 30 minutes, followed by postexercise cooling for 30 minutes in cool laboratory conditions (ambient temperature = 24.9 ± 1.8°C, relative humidity = 39% ± 10%). Patients or Other Participants: Twelve physically active men (age = 21.3 ± 1.1 years, height = 182.7 ± 7.1 cm, body mass = 76.2 ± 9.5 kg, sum of ± skinfolds = 50.5 ± 6.9 mm, body surface area = 1.98 ± 0.14 m2, V?O2max = 49.0 ± 7.0 mL·kg-1·min-1) participated. Intervention(s): Three experimental conditions, consisting of a PC17 jacket, a gel jacket, and no jacket. Main Outcome Measure(s): Core temperature (T C), mean skin temperature (TSk), and TC cooling rate (°C/min). Results: Mean peak TC postexercise was 38.49 ± 0.42°C, 38.57 ± 0.41°C, and 38.55 ± 0.40°C for the PC17 jacket, gel jacket, and control conditions, respectively. No differences were observed in peak TC cooling rates among the PC17 jacket (0.038 ± 0.007°C/min), gel jacket (0.040 ± 0.009°C/min), and control (0.034 ± 0.010°C/min, P > .05) conditions. Between trials, no differences were calculated for mean T Sk cooling. Conclusions: Similar cooling rates for all 3 conditions indicate that there is no benefit associated with wearing the PC17 or gel jacket. © by the National Athletic Trainers' Association, Inc.